Purification of C-phycocyanin from Spirulina - adsorption pretreatment options - Payne, Eric (Department of Chemical Engineering, 2024)
C-phycocyanin (C-PC) is an attractive blue pigment obtained from the cyanobacterium Spirulina and certain other species of microalgae. In recent years, C-PC has been used as a naturally derived colourant in cosmetic and food products due to the toxic effects of synthetic pigments. Cultivation of microalgae, like Spirulina, is well established, but there is scope to find new and more efficient ways of recovering the products they possess, including C-PC. There are many techniques which can be used to purify C-PC from Spirulina, where the choice of which is dependent on the desired C-PC application. Different applications require different degrees of C-PC purity, where this is measured as a ratio of the absorbance of C-PC in a sample relative to the total absorbance protein. Work was done at the Centre for Bioprocess Engineering Research (CeBER) to develop a process using aqueous two-phase separation (ATPS) and ammonium sulfate precipitation to generate C-PC for cosmetic use, which has a minimum purity requirement of 1.5. A patent was obtained before further work was conducted on this process to optimise certain aspects of it. Following on from this research, it was recommended that an adsorption pretreatment be incorporated into the process prior to the ATPS and precipitation to improve the C-PC purity entering these stages. This adsorption pretreatment was proposed to use chitosan and activated charcoal due to the potential they have shown in C-PC purification processes. They are both easy to use and are known to be efficient as adsorbents – chitosan due to its two distinct hydroxyl and carbonyl functional groups, and activated charcoal because of its high surface area. The goal of this research project was to test the pretreatment and understand what impacts it has on the ability of the overall process to generate cosmetic-grade C-PC reliably and efficiently. Leaching tests of the Carbocraft Spirulina used in this research project yielded an optimal period of 17 to 24 hours for the C-PC extraction from the Spirulina and showed that a cell disruption step was not necessary for this specific powder. Testing the adsorbents individually indicated that chitosan can selectively remove unwanted proteins while activated charcoal tends to adsorb indiscriminately. However, a significant improvement in purity is observed when they are used in combination. An attempt was made to optimise the concentrations of chitosan and activated charcoal as well as the adsorption pH and contact time through a central composite design. However, this does not provide any clear indication of optimal values, due to the high degree of experimental error and narrow range of purities. Running an adsorption prior to a polyethylene glycol (PEG) and citrate ATPS generated C-PC purities of approximately 1.5. However, the ATPS required a significant dilution to be effective and the C-PC recovery of this step was lower than 40%, making it potentially inefficient to scale up and impractical economically due to the high C-PC loss. A different process configuration was thus suggested, excluding ATPS but using ammonium sulfate precipitation followed by microfiltration and ultrafiltration. These two steps are included to reduce the levels of unwanted microorganisms and salts for cosmetic-grade C-PC. When feeding a crude extract with its concentration reduced with buffer by 50%, this purification train was able to consistently generate purities greater than 1.5. Additionally, by conducting activated charcoal adsorption in a packed column, the C-PC recovery of this stage of the process was improved and the low recovery as a consequence of using powdered activated charcoal in suspension and dead-end centrifugation can be avoided. C-PC powder was obtained by freeze drying samples which had been purified using the proposed process. These powdered samples were tested and found to have E-values (measure of colour intensity) competitive with commercially available products. The process was also shown to be robust and can handle variations in Spirulina feed. Ultimately, this confirmed that an adsorption step coupled with other standard purification techniques can be used to reliably generate cosmetic-grade C-PC with recoveries of 80% and above.